Distributed Coherent Mesh Beamforming (DisCoBeaM) for Robust Wireless Communications - Holtom, Jacob; Ma, Owen; Herschfelt, Andrew; Lenz, Isabella; Li, Yang; Bliss, Daniel W. (IEEE transactions on wireless communications, 2024)
We implement and experimentally demonstrate a distributed, phase-coherent, mesh relay network that executes spatiotemporal beamforming on a communications signal. Each single-antenna node of this mesh network amplifies, predistorts, and forwards its reception to a receiver. In this configuration, an incoherent network of N nodes enhances the received power of a signal of interest by a factor of N compared to a single-input single-output communications link. By synchronizing these distributed nodes and constructing a spatiotemporal beamformer, we increase this factor to a maximum of N {^{{2}}} and enable significant interference rejection capabilities. To achieve phase-coherence across the network elements, we execute a distributed synchronization algorithm using training data from the source node. We construct spatiotemporal beamformers by solving an MMSE optimization, which we continually reoptimize using new observations of training sequences and updated channel estimates. We present results from two over-the-air experimental demonstrations, one without and one with an external interferer. In the former, we demonstrate a 17.4 dB signal-to-noise ratio (SNR) improvement compared to the 18.1 dB theoretical bound for an eight-element network. In the latter, we demonstrate an 11.3 dB SNR improvement and a 14.6 dB interference reduction.